The Swedish National Election Study 2018 - CSES Edition - Andersson, Dennis; Hedberg, Per; Svensson, Richard; Oscarsson, Henrik (University of Gothenburg, 2021)
The National Election Survey 2018 was conducted in a collaboration between the Department of Political Science of University of Gothenburg and Statistics Sweden (SCB). This collaboration has covered all of the parliamentary elections, referendums and elections to the European Parliament since 1956. The Department of Political Science is responsible for the questionnaires, processing of data, coding and analyses. SCB is responsible for sampling and fieldwork.

Swedish National Election Studies participates in a wider international cooperation: Comparative Study of Electoral Systems (CSES). The cooperation means, among other things, that the same interview questions are asked not only in Sweden, but also in several other countries around the world. The Swedish National Election Studies participate in the CSES collaboration for the fifth time in connection to the election 2018.

Previously, the CSES questionnaires have been included in the Election Surveys' comprehensive post-election surveys. In connection to the election 2018 a new design was introduced. For the first time, a separate sample was drawn for the CSES edition of the Swedish National Election study, e.g. separate from the sample for the traditional National Election Survey. The separate CSES sample 2018 consists of a representative sample of 8,000 Swedish citizens aged 18-80 that are eligible to vote. Swedish citizens living abroad are not included in the sample.

The Swedish National Election Study 2018 - CSES Edition is a post-election survey that was conducted at the same time as the Election Survey 2018. The data collection was done through mail-surveys and web-surveys. The field period for the Swedish CSES Survey started on 10 September 2018 and lasted until 6 November 2018. The response rate was 47.3 percent.

Valundersökningen 2018 genomfördes i samarbete mellan Statsvetenskapliga institutionen, Göteborgs universitet och Statistiska centralbyrån (SCB). Samarbetet har pågått vid samtliga ordinarie riksdagsval, folkomröstningar och Europaparlamentsval sedan 1956. Statsvetenskapliga institutionen ansvarar för frågeformuleringar, framställning av frågeformulär, databearbetning, kodning och analyser. SCB ansvarar för urval och fältarbete.

Det svenska Valforskningsprogrammet ingår i ett internationellt samarbete, Comparative Study of Electoral Systems (CSES). Samarbetet innebär bland annat att samma intervjufrågor ställs i ett flertal länder runt om i världen. I samband med 2018 års val är det femte gången svenska Valforskningsprogrammet deltar i CSES-samarbetet.

Tidigare har CSES frågemoduler ingått i Valundersökningarnas omfattande eftervals-undersökningar. I samband med valet 2018 introducerades en ny design. För första gången drogs ett separat urval för CSES versionen av den svenska valundersökningen, skilt från urvalet för den traditionella Valundersökningen. Det separata CSES-urvalet 2018 utgörs av ett representativt urval av 8 000 röstberättigade svenska medborgare i åldern 18-80 år. Svenska medborgare boende i utlandet ingår inte i urvalet.

Svensk valundersökning 2018 - CSES versionen är en eftervalsundersökning som genomfördes samtidigt med Valundersökningen 2018. Datainsamlingen 2018 genomfördes via brevenkäter och webbenkäter. Fältperioden för den svenska CSES-undersökningen startade den 10 september 2018 och pågick fram till den 6 november 2018. Svarsfrekvensen var 47,3 procent.
Svensk valundersökning 2018 - CSES versionen
Keywords: public opinion; allmän opinion; attitudes; attityder; party identification; partiidentifikation; electors; väljare; political parties; politiska partier; Political behaviour and attitudes; Politiska beteenden och attityder; Elections; Val; Political Science; Statsvetenskap